The Impact of Macroeconomic Variables on Corporate Performance - What Shareholders Ought to Know? - Lars Oxelheim (The Research Institute of Industrial Economics (IUI), 2002)
Increased integration and growing macroeconomic fluctuations require more attention to be paid to the link between the noise that these fluctuations represent and the companys own development. For many reasons management must weed out the effects of the noise so as to obtain a clear picture of the long-term sustainable profits, and thus a picture of how the companys intrinsic competitiveness is fostered. An understanding of the effects of the fluctuations also provides the basis for risk assessment. How far, then, should this new view of corporate performance be extended to outsider shareholders? Current reporting practice does not provide these shareholders with an adequate idea of the character and magnitude of the macroeconomic impact on the company. IAS 1 (rev. 1997) indicates that an improvement in this important area may be in the offing. This paper discusses four different interpretational levels of this standard and what these levels mean in terms of relevant information transmitted to outsider shareholders.
Keywords: D81; M20; M21; M41; 330; External Reporting; Corporate Performance; Macroeconomic Fluctuations; MUST-analysis; Unternehmenserfolg; Shareholder Value; Theorie